TANTANGAN ERA GLOBALISASI TERHADAP MANAJEMEN PERGURUAN TINGGI - Maturbongs, Yoseph Hendrik (Jurnal Administrasi dan Kesekretarisan, 2019)
Education as a basic milestone in the development of human resources in the current era of globalization, must be a mainstay to produce competitive intellectuals. Compared to other countries in ASEAN, Indonesia still has a high unemployment rate and a low level of work productivity. Globalization, which is supported by accelerating rapid technological development, has eliminated the limits of the economy, trade, and displacement of human resources. How higher education faces the challenges of globalization is important to anticipate. This study will examine this through the literature review by reviewing the facts, describing the theories involved, analyzing and then concluding. Management of tertiary education as a major component of management of educational institutions must be carried out in an integrated manner towards the institution and its activities. Planned, organized, directed, and measurable management must always be aligned with the acceleration and challenges of globalization from all aspects. Generation characteristics, organizational performance and culture, flexibility and innovation, as well as information technology adaptability are critical factors that must always be developed and harmonized. The challenges identified for higher education management in facing the globalization era are, renewal, organizational communication, strategy, innovation and investment in physical and non-physical assets. In facing these challenges, the issue of globalization must always be aligned with the vision and mission, a clear and focused future orientation, developing people as a whole, consistently, serving the community as a whole, and aligning technology to human resources and business processes.Pendidikan sebagai tonggak dasar pengembangan sumber dayaÂ  manusia dalam era globalisasi saat ini, haruslah menjadi andalan untuk menghasilkan insan-insan cendikia yang kompetitif. Dibandingkan dengan beberapa negara di ASEAN, Indonesia masih memiliki tingkat pengangguran yang cukup tinggi, serta tingkat produktivitas kerja yang rendah. Globalisasi yang didukung dengan percepatan perkembangan teknologi yang sedemikian cepat telah meniadakan batas-batas ekonomi, perdagangan, dan perpindahan sumber baya manusia. Bagaimana pendidikan tinggi menghadapi tantangan globalisasi tersebut menjadi hal yang penting untuk diantisipasi. Telaah ini akan mengkaji hal tersebut melalui literatur review dengan mengkaji fakta yang ada, memaparkan teori yang berkaitan, menganalisa dan kemudian menyimpulkan. Manajemen pendidikan tinggi sebagai komponen utama pengelolaan institusi pendidikan, harus dilakukan secara terintegrasi terhadap kelembagaan maupun aktivitasnya. Pengelolaan secara terencana, terorganisir, terarahkan, dan terukur, harus selalu diselaraskan dengan percepatan dan tantangan globalisasi dari segala aspek. Karakteristik generasi, kinerja dan budaya organisasi, fleksibilitas dan inovasi, serta adaptibilitas teknologi informasi menjadi faktor-faktor kritis yang harus selalu dikembangkan dan diselaraskan. Tantangan yang teridentifikasi bagi manajemen pendidikan tinggi dalam menghadapi era globalisasi adalah, pembaharuan, komunikasi organisasi, strategi, inovasi dan investasi terhadap aset fisik maupun non-fisik. Dalam menghadapi tantangan tersebut maka isu globalisasi harus selalu diselaraskan dengan visi misi, orientasi masa depan jelas dan terarah, mengembangkan manusia secara utuh, konsisten, melayani masyarakat secara menyeluruh, serta penyelarasan teknologi terhadap sumber daya manusia dan proses bisnis.